2019
DOI: 10.1111/1471-0528.15848
|View full text |Cite
|
Sign up to set email alerts
|

Peripartum interventions resulting in reduced perinatal mortality rates, and birth asphyxia rates, over 18 years in a tertiary centre in South India: a retrospective study

Abstract: Objective To study the changes in the rates of perinatal mortality, birth asphyxia, and caesarean sections in relation to interventions implemented over the past 18 years, in a tertiary centre in South India. Design Retrospective study. Setting Labour and maternity unit of a tertiary centre in South India. Population or sample Women who gave birth between 2000 and 2018. Methods Information from perinatal audits, chart reviews, and data retrieved from the electronic database were used. Interventions implemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The overall incidence of BA reported in developed countries ranges from 1.6 to 24% varying by the type of study (single or multicenter or population based) and the operational definition of BA [22][23][24]. Multi-centric study in South India reported incidence of 24% [25] and 36% in a single center study in Nepal [26]. Similar, incidence of BA has been reported from systematic reviews and metaanalysis in Africa range from 15.9 to 22.3% [12,23,27].…”
Section: Discussionmentioning
confidence: 59%
“…The overall incidence of BA reported in developed countries ranges from 1.6 to 24% varying by the type of study (single or multicenter or population based) and the operational definition of BA [22][23][24]. Multi-centric study in South India reported incidence of 24% [25] and 36% in a single center study in Nepal [26]. Similar, incidence of BA has been reported from systematic reviews and metaanalysis in Africa range from 15.9 to 22.3% [12,23,27].…”
Section: Discussionmentioning
confidence: 59%
“…Not all studies were focused solely on evaluation of CTG training: Nine studies considered CTG training as a component of much wider organisational changes and restructuring (Appendix S3 ). 37 , 49 , 60 , 62 , 63 , 64 , 70 , 72 , 86 It was not possible to specifically assess the impact of CTG training alone in these studies, and the components and outcomes reported in these organisational interventions varied markedly (Appendix S3 ). We did not identify any studies that evaluated the impact of CTG training on the use of resources.…”
Section: Resultsmentioning
confidence: 99%
“…We identified 64 studies that met our inclusion criteria (Figure 1) reported across 65 papers (two papers reported different outcomes from the same study) 23–86 . One relevant study protocol was not included because the study is still ongoing 87 .…”
Section: Resultsmentioning
confidence: 99%
“…and 2015, the perinatal mortality rate changed from 22.3 to 17.4 per thousand births, with the southern region having the lowest rate and the northeast the highest, with values of 15.4 and 21.2, respectively [6][7][8] . Several authors point out risk factors associated with perinatal mortality, evidencing avoidable causes closely related to the quality of care, ranging from situations arising from the quality of prenatal care, delivery and newborn care [6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%